On the Link between Foreign Aid and Growth in Developing countries: Array - Tefera, Mamo; Nicholas, Odhiambo (Acta Universitatis Danubius. Œconomica, 2020)
Objectives: This study aims at exploring the debates on the aid-growth nexus from both a theoretical and empirical perspective. Prior Work: Despite the hot debate on whether aid works for growth, the increasing trends of aid flows to developing countries motivates the current study for re-visiting such debates. Approach: The study uses a detailed survey of both theoretical and empirical literature on the aid-growth nexus. Results: This review found that the aid-growth nexus is the most empirically researched area, and yet evidence remains inconsistent and controversial. Two lines of debate are identified: aid effectiveness (aid proponents) and aid ineffectiveness (aid opponents). While aid proponents argue that aid positively affects growth, aid opponents found that aid has either a negative or null impact on growth. Implications: Contrary to the scholarly debates, the common belief among donors is that the effect of aid on growth is positive and aid flows to the productive/economic sectors is more growth-enhancing. Thus, aid-financing decisions by donors and policy makers should take this aspect into account. Value: Besides exploring the debates, this review discusses the reasons behind the inconsistent evidence on the aid-growth nexus and highlights the relevant methodological approaches to address this problem, mostly aid endogeneity.